ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TELUR AYAM RAS DI PASAR 16 ILIR KOTA PALEMBANG - Unmabsi, Vortuna; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
This study aims to find out how the influence of variable prices of chicken eggs breeds, the price of other goods (tempe), and income to the demand for chicken eggs breeds in the market 16 Ilir Palembang city. The research method used is survey method and sample withdrawal method using accidental sampling. The data collection method used in the study was interviews to respondents who found as many predetermined samples using pre-prepared questionnaire tools. Data processing using multiple linear regression analysis. From the results of the study that the results of the analysis of factors that affect the demand for breed chicken eggs in the market 16 Ilir Palembang city, there is a significant influence on the price of chicken eggs breeds, haraga other goods (tempe ), and simultaneous income to the demand for chicken eggs breeds in the market 16 Ilir Palembang city, and there is a significant influence on the price of chicken eggs breeds and revenue partially to the demand for chicken eggs breeds in the market 16 Ilir Palembang city, then there is no significant contribution of the price of other goods (tempe/tofu) partially to the demand for chicken eggs breeds in the market 16 Ilir Palembang city.